2021
DOI: 10.1007/s40266-021-00862-6
|View full text |Cite
|
Sign up to set email alerts
|

Ghent Older People’s Prescriptions Community Pharmacy Screening (GheOP3S)-Tool Version 2: Update of a Tool to Detect Drug-Related Problems in Older People in Primary Care

Abstract: Background The Ghent Older People’s Prescriptions community Pharmacy Screening (GheOP 3 S)-tool was developed in 2016 as a screening tool to detect drug-related problems (DRPs) and to help in performing medication reviews in older people (≥ 65 years). Objective This study aimed to revise and update the GheOP 3 S-tool. Methods Users’ comments were collected to improve the usability and appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 44 publications
0
28
0
1
Order By: Relevance
“…The majority of the included lists were for older people generally, although lists were identified specifically for older people living with dementia, 26 heart failure, 27,28 frailty 29 or in residential aged care 30,31 . Older people were defined as people aged 65 years and older for most of the lists ( n = 21), 26,31‐49 while two lists specified 70 years and older, 30,50 and one list specified 75 years and older 51 . Older people were not defined by age in the remaining papers ( n = 11) 27‐29,52‐59 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the included lists were for older people generally, although lists were identified specifically for older people living with dementia, 26 heart failure, 27,28 frailty 29 or in residential aged care 30,31 . Older people were defined as people aged 65 years and older for most of the lists ( n = 21), 26,31‐49 while two lists specified 70 years and older, 30,50 and one list specified 75 years and older 51 . Older people were not defined by age in the remaining papers ( n = 11) 27‐29,52‐59 …”
Section: Resultsmentioning
confidence: 99%
“…Most lists were intended for use in clinical practice; however, some studies also indicated alternative purposes, which included use as a teaching tool, decision aid, for medication reviews, quality assessments or for applying to epidemiological data (Table 1). Multiple studies were conducted in Canada ( n = 4), 31,40,53,54 United States ( n = 3), 32,44,47 Korea ( n = 3), 37‐39 Norway ( n = 2), 30,50 Spain ( n = 2), 49,55 Australia ( n = 2), 26,33 Belgium ( n = 2), 35,58 Thailand ( n = 2), 27,46 Ireland ( n = 2), 28,29 Italy ( n = 1), 60 Japan ( n = 1), 43 Taiwan ( n = 1), 34 Turkey ( n = 1), 52 Germany ( n = 1), 36 China ( n = 1), 59 France ( n = 1) 51 and Hong Kong ( n = 1) 48 . Four studies were collaborative works between multiple countries 42,45,56,57 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is crucial to investigate the ways to include additional information about the PIMs listed in both criteria in the design of the integrated PIM tool, e.g., “positive” list of active substances or medication classes (A- and B-class medications) for certain indications by EURO-FORTA, as well as suggestions for dose and/or treatment duration adjustments (also in relation to hepatic and renal function), and therapeutic alternatives for PIMs based on the EU(7)-PIM list. Lastly, the authors discuss the future option to include recommendations concerning the use of a similar alternative PIM checklist [e.g., the Ghent Older People’s Prescriptions Community Pharmacy Screening (GheOP3S)‐Tool Version 2] for identification of the grey PIMs or any other possible discrepancies ( Foubert et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This monitoring role by community pharmacists in primary care directly aligns with a broader international trend towards the provision of professional pharmacy services, which came to prominence in the 1990s with the advent of “pharmaceutical care” [ 7 ]. Pharmaceutical care has been defined as ‘the pharmacist’s contribution to the care of individuals in order to optimise medicines use and improve health outcomes’ [ 8 ], highlighting the need for routine monitoring of the use of medicines within healthcare systems [ 9 ].…”
Section: Introductionmentioning
confidence: 99%